2023
DOI: 10.1111/hae.14779
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilia B, severe childhood obesity and other extra‐haematological features associated with similar 4Mb‐deletions on Xq27: Clinical findings, molecular insights and literature update

Abstract: Introduction: Haemophilia B (HB) is associated with pathogenic variants in F9. Hemizygous deletions encompassing the entire F9 and proximate genes may express extra-haematological clinical phenotypes. Aim: To analyse the genotype/phenotype correlations in two unrelated boys with severe early childhood obesity (SCO), global developmental delay (GDD) and similar bleeding phenotype associated with comparable Xq27 deletions spanning the entire F9 and proximate genes, and characterise the pathogenic events estimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…According to Radic et al patients develop extra-hematologic phenotypes such as partial hypopituitarism, intellectual disability, and developmental delay when the deletion region encompasses the SOX3 gene. 15 However, proband 1 had a chromosomal deletion affecting multiple genes, including SOX3 , but did not exhibit any unique medical history records beyond HB. One possible explanation could be attributed to compensatory mechanisms within the genome that can mitigate the functional loss of the SOX3 gene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Radic et al patients develop extra-hematologic phenotypes such as partial hypopituitarism, intellectual disability, and developmental delay when the deletion region encompasses the SOX3 gene. 15 However, proband 1 had a chromosomal deletion affecting multiple genes, including SOX3 , but did not exhibit any unique medical history records beyond HB. One possible explanation could be attributed to compensatory mechanisms within the genome that can mitigate the functional loss of the SOX3 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested the involvement of DNA repair-based mechanisms, such as nonhomologous end joining and nonallelic homologous recombination (NAHR), and DNA replication-based mechanisms like Fork Stalling and Template Switching/microhomology-mediated break-induced replication (FoSTeS/MMBIR) in F9 -related SVs. 15 16 17 However, recurrent NAHR rearrangements mediated by low-copy repeats (LCRs), similar to the intron 22 inversion of F8 , have not been identified in structural rearrangements involving F9 to date.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation